Asset pricing, habit memory, and the labor market - Ivan Jaccard (European Central Bank (ECB), 2010)
This article studies the asset pricing and the business cycle implications of habit formation in a production economy with capital adjustment costs and endogenous labor supply. A specification of internal habit in the mix of consumption and leisure which minimizes the wealth effect on labor supply is introduced into an otherwise standard real business cycle model. This mechanism enhances the model's ability to explain asset pricing puzzles.
Keywords: G12; E32; J22; 330; adjustment costs; equity premium puzzle; Labor supply; Equity-Premium-Puzzle; Arbeitsmarkt; CAPM; Theorie